2011
DOI: 10.1097/gim.0b013e31820c685b
|View full text |Cite
|
Sign up to set email alerts
|

Reflex fluorescent in situ hybridization testing for unsuccessful product of conception cultures: A retrospective analysis of 5555 samples attempted by conventional cytogenetics and fluorescent in situ hybridization

Abstract: Introduction:The use of chromosome analysis on products of conception from spontaneous abortions is recommended to identify a genetic etiology. However, 20% of products of conception cultures are unsuccessful due to microbial contamination or lack of viable dividing cells. Our laboratory implemented a reflex fluorescent in situ hybridization (FISH) assay to detect numeric chromosome abnormalities for unsuccessful cultures. Materials and Methods: All products of conception samples were simultaneously processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 42 publications
7
91
4
1
Order By: Relevance
“…We obtained a 90.3% rate of successful chromosome analysis, which is higher than the rates reported in some of the previous large studies that performed cytogenetic ( Table 6 ) [Eiben et al, 1990;Menasha et al, 2005;Shearer et al, 2011;Jenderny, 2014;Wang et al, 2014]. Our success rate is similar to the 92.4% rate obtained in the recent study of Sahoo et al [2017] using mostly SNP-array analysis in fresh tissue samples, but lower than the 99.9% rate reported by Levy et al [2014], although in this case 22% of the samples were not valid due to maternal cell contamination.…”
Section: Success Rate Abnormality Rate and Overall Frequenciescontrasting
confidence: 50%
“…We obtained a 90.3% rate of successful chromosome analysis, which is higher than the rates reported in some of the previous large studies that performed cytogenetic ( Table 6 ) [Eiben et al, 1990;Menasha et al, 2005;Shearer et al, 2011;Jenderny, 2014;Wang et al, 2014]. Our success rate is similar to the 92.4% rate obtained in the recent study of Sahoo et al [2017] using mostly SNP-array analysis in fresh tissue samples, but lower than the 99.9% rate reported by Levy et al [2014], although in this case 22% of the samples were not valid due to maternal cell contamination.…”
Section: Success Rate Abnormality Rate and Overall Frequenciescontrasting
confidence: 50%
“…Whole-chromosome aneuploidies are the most common etiology. [4][5][6][7][8][9][10][11] Fetal chromosomal abnormalities account for approximately 8-10% of intrauterine fetal demises occurring after 20 weeks of gestation and/or stillbirths occurring in the second or third trimester. 9,12 The etiologic analysis of pregnancy loss can provide important information for medical management, reproductive counseling, and supportive patient care.…”
Section: Introductionmentioning
confidence: 99%
“…9,[15][16][17][18][19] Additionally, the quality and viability of POC samples are critical for successful cell culture and karyotype analysis. 4,8 Second, even when tissue is dissected carefully, there is always the risk of an erroneous result due to maternal cell contamination (MCC). Specifically, selective overgrowth of maternal cells during culture can result in a normal female karyotype even in the presence of an underlying fetal chromosome abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Few articles have evaluated the correlation between an anembryonic sac and chromosomal abnormalities, and their results were inconsistent [2,3,5,29] (Table 3). Our study found that the risk of chromosomal abnormality with this type of ultrasound finding was not significantly higher than the risk associated with other abnormal ultrasound findings.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…Over 95 % of miscarriages occur in the first trimester, and more than half of spontaneous miscarriages result from chromosomal abnormalities, mostly aneuploidies [2][3][4]. Of these, the most common abnormalities are autosomal trisomies (60 %), followed by monosomy X (20 %) and polyploidy (20 %) [5,6].…”
Section: Introductionmentioning
confidence: 99%